Press statement
015a_0028_001 Spain PRESS STATEMENT. 1st September 1936. The Rt. Hon. Arthur Greenwood M.P., Sir Walter Citrine, Secretary of the T.U.C. Mr. J.S. Middleton, Secretary of the Labour Party visited the Foreign Office this afternoon, and in the absence of Mr. Eden interviewed Lord Cranborne regarding the position of the non-intervention agreements and the machinery which it was proposed to established to carry them into effect. They expressed their disquiet concerning the present situation, and emphasised the importance of immediate steps being taken to ensure that the agreements were being effectively carried out. Lord Cranborne stated that the Government were fully alive to the importance of an early meeting of the proposed committee to supervise the agreements, and were collaborating with the French Government to that end. 292/946/15a/28